Policy for Improving Digital Literature in Indonesia SDGs Based - Sandya Mahendra; Engine Kubota; Anis Nur Fauziyah MS; Tiara Dwiyanti; Filzah Ilda Syafirah (UM Purwokerto Press, 2022)
Indonesia is one of the countries that participates in the activities of the United Nations (UN) in order to implement mutual agreements in order to achieve Suistanable Development Goals (SDGs). To fulfill SDGs, needed a lot efforts, example like to increase digital literacy capabilities. The aims of this study are 1) To describe digital literacy policies in Indonesia. 2) Describe the concept of a digital literacy policy based on SDGs. This research used normative legal research method which in there using way examining a few of library materials and a few of secondary data that related with the topic of this research. This research besides used normative legal research method, also using statute approach and conceptual approach for approaching the topic and the materials. Following from Gilster, to understand and use information from various formats, we can use digital literacy. Not just that, Gilster also told if reading with meaning and understanding is one of literacy concept, not just about ability to read. In digital literacy we not meet keystrokes, but mastery of any ideas. The government's policy in increasing digital literacy is stated in the ITE Law and the Ministry of Communication and Information of the Republic of Indonesia in 2021 takes preventive steps, namely launching a digital literacy movement for 12.4 million people in 34 provinces. The concept of digital literacy has two points of view, first literacy by computer. That is literacy which is person use their ability to operating the computer for literacy. And then the second is literacy by information, which is person use their ability to use, package find, and evaluate and disseminate digital information correctly. According to the GLN Team of the Ministry of Education and Culture, there are have 4 (four) base principles for developing namely understanding, and then digital literacy, interdependence, social factors, and curation.